Analisis Faktor-Faktor Yang Mempengaruhi Customer Satisfaction Terhadap Buying Behavior Produk Ogb Pada Saluran Distribusi Farmasi - Alif Saputra Matellow; Rina Anindita (Faculty of Economics and Business, University of Pancasakti Tegal, 2025)
An important aspect that must be a concern for companies to win market competition is the customer satisfaction variable and its implications on the buying behavior variable. The purpose of this study is to analyze the factors that influence the customer satisfaction variable on the buying behavior variable of OGB products in the pharmaceutical distribution channel. The factors in question are product price, service quality, customer perceived value, and trust. The study was conducted at 107 outlets including conventional pharmacies, pharmacies in hospitals, and pharmacies in clinics as respondents in the Bekasi area for one month. The collected data were processed through SEM-PLS analysis. The results of this study prove that the product price variable was found to have an effect on the buying behavior variable, but did not affect the customer satisfaction variable, then the service quality variable was found to have an effect on the trust variable and the customer satisfaction variable, then the customer perceived value variable was found to have an effect on the trust variable, but did not affect the customer satisfaction variable, then the trust variable was found to have an effect on the customer satisfaction variable, then the customer satisfaction variable was found to have an effect on the buying behavior variable. The managerial implications of the research results that can be applied by pharmaceutical companies include setting fair product prices, maximizing good service quality, maintaining the positive value felt by outlets as customers towards the company, maintaining outlet trust, and striving to achieve customer satisfaction in every transaction.